The Role of Real Work Lectures to Build Villages Towards Dignified Destinations (Case study of Engineering Students at Mpu Tantular University KKN 2022) RT 02, RW 04, Kampung Lame Village, Sukasari Village, Rumpin District, Bogor Regency, West Java Province - Edison Hotaguan Manurung; ML. Saragih; Abdul Mubarok; Andri Waskito; Kerlima Hutagaol; Agung Setyawan; Siti Retno Fatmawati; Ahmad Fajar Maulana; Fandi Dwi Hermawan; Imron Natalius Panjaitan; Muhammad Nasheer Amri (Indonesian Journal of Advanced Social Works, 2022)
Community empowerment is defined as an activity to increase the contribution of the community in meeting the necessities of life and solving problems that exist in society. Activities are carried out through the KKN program which is an activity based on community service to develop student empathy for the condition of society and the environment. The KKN was carried out in Rumpin, Bogor Regency, West Java Province with service methods such as education, training for Bina Trampil Plus Middle School students and the surrounding community. The results show that there is a positive response from the community by carrying out teaching activities at Bina Trampil Plus Middle School, namely the introduction of basic computers such as introduction to computer hardware, knowledge of Microsoft Office (Microsoft Word and Microsoft Excel), and basic web programming (HTML and CSS).